Civil Liability for Artificial Intelligence in Electronic Contracts: A Conceptual Framework in Indonesian Law - Lilisen Lilisen; Narpika Yendra; Pudji Natalya M; Hendy Liusgria; Tjhang Kian On; Hetiyasari Hetiyasari (PDIH Untag Semarang, 2025)
The integration of Artificial Intelligence (AI) into electronic contracts introduces new legal challenges, particularly regarding civil liability for losses caused by algorithmic errors or system failures. This study aims to examine the mechanisms for enforcing such liability within the Indonesian legal framework by analyzing both tort-based responsibility and contractual liability arising from electronic transactions. Using a normative juridical method supported by statutory, conceptual, and comparative approaches, this research evaluates the relevant legal provisions, liability principles, and international practices. Under Article 1365 of the Civil Code, parties controlling or benefiting from AI may be held liable if negligence leads to harm. Meanwhile, the electronic information and transactions Law and Government Regulation 71 of 2019 provide the foundation for contractual claims, including obligations related to system reliability, data integrity, and digital audits. The findings show that enforcing liability requires clear causal proof, algorithmic transparency, and the ability to assess both material and non-material losses. Comparative cases such as Deloitte Australia, DoNotPay, and OpenAI demonstrate the global relevance of due diligence, algorithm auditing, and human accountability. This study concludes that Indonesia’s existing legal framework offers adaptive mechanisms for addressing AI-related losses, while emphasizing the need to strengthen regulatory clarity and accountability standards in the digital era.